Mathematical Modelling of the Effects Funding on HIV Dynamics Among Truckers and Female Sex Workers Along the Kenyan Northern Corridor Highway - Kimulu, Ancent Makau; Mutuku, Winifred Nduku; Mwalili, Samuel Musili; Malonza, David; Oke, Abayomi Samuel (My University, 2022)
The Southern and Eastern parts of Africa are the most hit by HIV/AIDS in the world and a huge financial commitment is required to control the spread of the disease. Of these countries, Kenya and South Africa have been able to increase prevention and treatment services due to their financial commitment to fighting the epidemic. However, studies have shown that most of the financial commitment comes from private donors and the private sectors are recently becoming reluctant to release funds. It is therefore important to ensure that the available funding is effectively utilised. Studies in 2018 show that infections occurred mostly among the key populations on the Kenyan Northern Corridor highway; such as sex workers and truckers. Moreso, transactional sex which involves cash transfer is the main mode of transmission of HIV/AIDS along the Northern corridor highway in Kenya. In this paper, we study the effect of funding on HIV transmission between truckers and female sex workers. A mathematical model with funding parameters is developed and analysed to determine the effects of funding on the HIV transmission dynamics between truckers and female sex workers. The reproduction number is obtained using the next-generation matrix and the conditions for the stability of the equilibrium points are established. The model is fed into the MATLAB ode45 solver and a numerical simulation is carried out. The results show that increasing circumcision funding reduces the rate of migration from the Susceptible class to the Infected class. Also, increasing treatment funding increases the Treatment class and reduces the overall number of AIDS-related.
Keywords: HIV/AIDS; Funding; Transmission Dynamics; Truckers; Female Sex Workers